2006
DOI: 10.1007/s10681-006-9134-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variability in vegetable amaranth (Amaranthus tricolor L for foliage yield and its contributing traits over successive cuttings and years

Abstract: Twenty nine strains of vegetable amaranth (Amaranthus tricolor L.) were grown for two successive seasons to study different selection parameters for foliage yield and its nine contributing morphological and quality traits. The strains AV-38 (5.06 kg/plot) and AV-31 (5.04 kg/plot) recorded highest foliage yield, followed by AV-30 (4.78 kg/plot) and AV-23 (4.70 kg/plot). The protein and carotenoid content averaged 1.24 ± 0.03 mg/100 mg and 0.83 ± 0.02 mg/g respectively. The leaves of A. tricolor also have consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
101
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 11 publications
14
101
0
3
Order By: Relevance
“…Beside its adaptable nature in various climatic conditions, the amaranth plant also has important nutritional and medicinal properties (Lakshmi and Vimala, 2000). Due to use of amaranth as vegetable and grain crop, it can be a cheap alternative rich source of protein and nutrient for poor people in developing countries (Prakash and Pal 1991;Prakash et al, 1995;Shukla et al, 2006). The protein component of amaranth is quite close to the level recommended by the FAO/WHO for balance diet in human.…”
Section: Issn: 2319-7706 Volume 6 Number 8 (2017) Pp 2459-2470mentioning
confidence: 97%
See 1 more Smart Citation
“…Beside its adaptable nature in various climatic conditions, the amaranth plant also has important nutritional and medicinal properties (Lakshmi and Vimala, 2000). Due to use of amaranth as vegetable and grain crop, it can be a cheap alternative rich source of protein and nutrient for poor people in developing countries (Prakash and Pal 1991;Prakash et al, 1995;Shukla et al, 2006). The protein component of amaranth is quite close to the level recommended by the FAO/WHO for balance diet in human.…”
Section: Issn: 2319-7706 Volume 6 Number 8 (2017) Pp 2459-2470mentioning
confidence: 97%
“…The protein component of amaranth is quite close to the level recommended by the FAO/WHO for balance diet in human. The protein in leaf is up to 14.3g/kg with an average of 12.4g/kg (Shukla et al, 2003(Shukla et al, , 2006Prakash and Pal 1991). A large number of necessary minerals have also been reported in amaranthus.…”
Section: Issn: 2319-7706 Volume 6 Number 8 (2017) Pp 2459-2470mentioning
confidence: 99%
“…Studies on A. tricolor showed that chlorophyll content and ascorbic acid are the major contributing traits of PC1 (Shukla et al, 2010). Chlorophyll content may affect foliage yield with the increment of photosynthetic rate by increasing the vegetative growth of amaranth (Shukla et al, 2006). In contrast, PC2 extracted the cultivars under leaf color b * value, betacyanins and betalains content.…”
Section: Mean Plasticity Indexmentioning
confidence: 98%
“…These dual-purpose plants supply not only nutritious grains but also tasty, leafy vegetables consumed all over the world, as both human food and animal feed. The leaves of amaranth constitute an inexpensive and rich source of protein, carotenoids, vitamin C, dietary fibre, calcium, iron, zinc, magnesium and phosphorus (Shukla et al, 2006;Ozbucak et al, 2007). Amaranth protect against several disorders such as defective vision, respiratory infections, recurrent colds, retarded growth, functional sterility, bleeding tendencies, leucorrhoea, and premature ageing (Bakhru, 2007).…”
Section: Introductionmentioning
confidence: 99%